"We Are Small, But We Have Jobs": A Profile of the Labour Activities of Children and Youth in South Africa. Issue 3 (2nd October 2018) - De Wet, Nicole; Ewemade, Jude
ABSTRACT: Starting from young ages, children and youth are dealing with adult problems such as poverty and food security. For this reason, children and youth enter the labour market earlier than expected, compromising their scholastic performance and future earnings if they drop out of school. This study profiles the children and youth of South Africa who are engaged in labour market activities using a nationally representative cross-sectional survey. The characteristics of this sub-population are shown, as well as the types of work, remuneration and co-activities are investigated. Most of the children and youth engaged in labour activities are not in school, and many are working as street vendors. Also, the likelihood of engaging in labour activity is high if there is no father in the household. Steps need to be taken to keep children in school and not working in the informal economy.